Daily performance of a solar hybrid regenerative gas turbine in Colombia (2021)
This work presents the evolution of the operation of a regenerative hybrid solar gas turbine in an average day of the year. The system is evaluated by means of a thermodynamic model that includes a solar concentrated heliostat field solar concentrator with central receiver, a combustion chamber, and the thermal engine. The model is applied in Barranquilla, Colombia using local temperature and the solar radiation estimated with a theoretical model. Power output, the global efficiency and thermal engine efficiency are estimated. Additionally, to estimate the temperatures in different states of the cycle with and without regenerator. Finally, the impact of the regenerator is evaluated, which can increase the temperature of the solar receiver by up to 13.6%, and the inlet temperature to the combustion chamber increases by 17.3% at noon, when solar radiation is maximum.